Variation in perceived providers of ambulatory physical therapy in the United States, 2009–2012: An analysis using data from the Medical Expenditure Panel Survey. (4th March 2019) - Brooks, Gary; Dolphin, Michelle; Rufa, Adam
ABSTRACT: Introduction : Little is known about public perception of physical therapy (PT) delivery by type of provider in the United States (US).Purpose : This study aimed to describe differences in ambulatory PT visits and expenditures according to perceived provider type, and to determine if visits and expenditures varied by provider type.Methods : This study employed the Medical Expenditure Panel Survey (MEPS), which is a nationally representative survey of US households that used a complex, stratified, cluster sample design. Data from cross-sectional samples over 4 years of the MEPS Household Component were used to study adults with musculoskeletal conditions who reported receiving ambulatory PT. National-level, average annual estimates of numbers of visits, and reported total expenditures by perceived provider type were computed. Associations between perceived provider type and visits and expenditures were determined by linear regression, accounting for the sample design, and adjusting for demographic and clinical covariates.Results : Estimated annual perceived PT visits were 60.00 million with physical therapists, 39.66 million with non-physical therapist providers, and 20.66 million with multiple providers. Estimated annual expenditures for PT were $9.37 billion with physical therapists, $4.62 billion with non-physical therapist providers, and $3.09 billion with multiple providers. Compared with non-physical therapist providers, physical therapist provider status and multiple provider status were associated with higher numbers of visits and expenditures.Conclusion : Non-physical therapist providers are responsible for a substantial amount of PT delivery in the US. Numbers of visits and total expenditures varied by the type of provider delivering PT.